Neurovascular protection of cilostazol in stroke‐prone spontaneous hypertensive rats associated with angiogenesis and pericyte proliferation. Issue 3 (21st December 2013) - Omote, Yoshio; Deguchi, Kentaro; Kono, Syoichiro; Liu, Ning; Liu, Wentao; Kurata, Tomoko; Yamashita, Toru; Ikeda, Yoshio; Abe, Koji
<x xml:space="preserve">Abstract</x> Stroke is the major cause of death and decrease in the activities of daily living. This study sought to evaluate the effects of commonly used antiplatelet drugs on spontaneous cerebral infarction in relation to neurovascular protection associated with angiogenesis and pericyte proliferation. Stroke‐prone spontaneously hypertensive rats (SHR‐SP) were treated with vehicle, aspirin, clopidogrel, or cilostazol from 8 to 10 weeks of age. The interaction of neurovascular components among endothelial cells, pericytes, and astrocytic endfeet were immunohistochemically examined in brain sections. Angiogenesis associated with vascular endothelial growth factor receptor 2 (VEGFR2) and pericyte proliferation were also examined immunohistochemically. The expression and activity of matrix metalloproteinase 9 (MMP‐9) were assessed immunohistochemically and by gelatin zymography. Among the antiplatelet drugs, cilostazol preserved the neurovascular unit (NVU) by preventing astrocytic endfeet or pericytes from pathological detachment found in the vehicle and aspirin treatment. Cilostazol also inhibited the expression and activity of MMP‐9, which led to protection of the NVU. Furthermore, in the periinfarct area, cilostazol increased VEGFR2 expression, promoting angiogenesis through proliferation of pericytes. The present study showed a strong protection of NVU integrity by cilostazol and the promotion of angiogenesis by stimulating both endothelial VEGFR2 expression and pericyte proliferation. In addition to the antioxidative effect, these pleiotropic effects of cilostazol contribute to reduce spontaneous infarct volume and preserve motor and cognitive function in SHR‐SP. © 2013 Wiley Periodicals, Inc.